The Resistant Soybean-Aphis glycines Interaction: Current Knowledge and Prospects - Natukunda, Martha I.; MacIntosh, Gustavo C. (Frontiers in Plant Science, 2020)
Soybean aphids (Aphis glycines Matsumura) are invasive insect pests of soybean, and they cause significant yield losses. Resistance to soybean aphids is conferred by Resistance to Aphis glycines (Rag) genes. Since the first discovery of aphid-resistant soybean genotypes in 2004, several studies have attempted to characterize Rag genes from aphid-resistant soybean genotypes. To date, 12 Rag genes and four quantitative trait loci for aphid resistance have been reported on soybean chromosomes 07, 08, 13, 16, and 17. Although candidate genes have been proposed for several discovered Rag loci, additional studies are needed to pinpoint, validate, and further explain the potential mechanisms of Rag gene action. A major challenge to utilizing host plant resistance is the discovery of virulent aphid biotypes that can colonize aphid-resistant soybean. This occurrence suggests the need for additional studies to devise strategies to enhance the effectiveness of aphid-resistant soybean. In this mini review, we discuss current knowledge on the resistant soybean-Aphis glycines interaction, potential mechanisms of Rag gene action, opportunities to discover new Rag genes, and prospects for utilization of host plant resistance to manage soybean aphids. A clearer understanding of host plant resistance to soybean aphids will guide researchers on strategies for developing soybean varieties with more durable aphid resistance, reducing the present challenge of virulent aphid biotypes.